PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS VII SMP ISLAM BAWARI TAHUN AJARAN 2019/2020 - Aidil Lisa Sabila; Abdussamad Abdussamad; Deden Ramdani (Universitas Tanjungpura, 2020)
Abstarct This study discusses the improvement of reading comprehension skill using the Cooperative Interated Reading and Composition (CIRC) method in class VII students of Bawari Islamic Middle School in 2019/2020 academic year. This study aim to describe the application of the Cooperative Interated Reading and Composition (CIRC) method in class VII students. This study carried out a descriptive study with qualitative and quantitative forms. The research was conducted in two cycles, starting with a pretest and continued with the implementation of cycle one and cycle two. Data collection is done by carrying out test in each research cycle. The results of the analysis showed tha the reading comprehension ability of students increased in each cycle, as evidenced by the pretest result with an average value of 62.13, cycle one with an average value of 69.13, and cycle two with an average value of 78.38.Keywords: Ability; Cooperative Integrated Reading and Composition (CIRC) ; Reading Comprehension.